THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF THE FORMATION FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE OF STUDENTS NON - LINGUISTIC UNIVERSITY - Musina S.K., Мусина С.К. (Рroblems of engineering and professional education, 2023)
In this paper current trends of "competence" and “competency” were investigated. The formation of the concept of knowledge has being presented for many years; skills include the theoretical basis, the definition of nomenclature, and the hierarchy of knowledge, skills, and methods of their formation, monitoring and evaluation. This concept is still fundamental to many tutors and teachers of secondary and higher educational institutions.